The Isotherm Studies of Cu (II) Adsorption in Kolong Bangka’s Water onto NaOH-Deacetylated Shrimp Shells Waste Chitin - Desy Yuliana Dalimunthe; Anisa Indriawati; Endang Setyawati Hisyam; Herman Aldila (Stannum : Jurnal Sains dan Terapan Kimia, 2023)
Isotherm models of Cu (II) adsorption in Kolong Bangka’s water onto NaOH-deacetylated shrimp shells waste chitin was studied. The extraction of chitin was carried out through three steps: deproteinization, demineralization and decolorization. The deacetylated shrimp shells waste chitin (DA-SW chitin) were prepared by the reaction of DA-SW chitin with NaOH at varying concentrations of 20, 40 and 60% (%W) with stirring for 1 hour at room suhue where the degree of deacetylation for varying NaOH concentrations were 65.72, 67.44 and 88.98%, respectively based on our previous research. Increasing the NaOH concentration causes the diffusion rate of OH- increase thus realizing the effectiveness of OH- attack on the carbonyl carbon group in chitin acetamide increasing so that the chitin deacetylation process becomes more effective. In order to study adsorbent equilibrium behaviour, Freundlich and Langmuir isotherm models were used based on Cu (II) adsorption data with variations in contact time 5, 10, 15, 20, 25, and 30 minutes. The results showed that the concentration of Cu (II) decreased with the increase of the degree of deacetylation and contact time. The optimum condition for the percentage of Cu (II) adsorption was achieved in DA-SW chitin with NaOH 60% (where the degree of deacetylation was 88.98%) during 30 minutes was 97.19%. The Cu (II) adsorption isotherm model in Kolong Bangka water onto DA-SW chitin is represented by the Freundlich isotherm model where the Cu (II) adsorption mechanism onto DA-SW chitin causes the formation of multilayer surface which may due to Van der Waals force.